Multiphase metering system - Henry, M (Chinese National Intellectual Property Administration, 2014)
A multi-phase fluid is passed through a Coriolis flowmeter and a watercut meter. The multi-phase fluid includes two phases during a first time period and three phases during a second time period. It is determined that the multi-phase fluid includes two phases during the first time period, and a first value of a parameter of the multi-phase fluid is determined using a value measured by the Coriolis flowmeter during the first time period. A second value of a parameter of the multi-phase fluid is determined using a value measured by the watercut meter during the first time period. The first value is compared to the second value, and it is determined, based on the comparison, that the first value and the second value are inconsistent with each other.